PENGARUH SANKSI PAJAK DAN PEMERIKSAAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Intan Kirana Amelia Vitaloka; Muhammad Sopiyana (Jurnal Nusa Akuntansi, 2026)
This study aims to understand how tax sanctions and audits conducted on taxpayers affect the level of compliance of individual taxpayers. This study is motivated by the need to increase compliance in order to support state revenue from the taxation sector. Using a qualitative approach, this study explores in depth the views, attitudes, and responses of taxpayers towards the application of sanctions and audit activities by the tax authorities.mData were obtained through in-depth interviews with a number of individual taxpayers, tax consultants, and employees of the Directorate General of Taxes. The results of the study indicate that the application of strict sanctions can have a deterrent effect, although its effectiveness depends on the level of understanding and awareness of taxpayers. On the other hand, tax audits are considered capable of increasing compliance if carried out fairly and transparently. This finding emphasizes the importance of a balance between rule enforcement and educational efforts in shaping tax compliant behavior among individual taxpayers.